2002
DOI: 10.1109/tmag.2002.803566
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the magnetic anisotropy in Fe-Si amorphous alloys

Abstract: transition metal. 3d electrons in transition metals have a much weaker spin-orbit interaction compared to the Rare Earths, and they interact more strongly with the crystal field which makes their orbital moments smaller so that their magnetism is dominated by the exchange interaction. In Transition MetalMetalloid (TM-M) alloys, the Metalloid (Si, B, P..) is introduced to amorphisize the TM structure. The exchange interaction is believed to still dominate in these compounds [2]. Their ferromagnetic correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Diaz et al [17] reported that in Fe-Si amorphous soft ferromagnetic films, due to large local anisotropy of Fe ions (10 6 J/m 3 ) caused due to structural disorder, a small degree in the orientational correlation of the local orbital moments can result in uniaxial anisotropy. By analogy, precipitation of even small fraction of Fe 2 B compound in CoFeB may contribute to the uniaxial anisotropy owing to its high magneto-crystalline anisotropy ( $ À4 Â 10 5 J/m 3 ) [15].…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al [17] reported that in Fe-Si amorphous soft ferromagnetic films, due to large local anisotropy of Fe ions (10 6 J/m 3 ) caused due to structural disorder, a small degree in the orientational correlation of the local orbital moments can result in uniaxial anisotropy. By analogy, precipitation of even small fraction of Fe 2 B compound in CoFeB may contribute to the uniaxial anisotropy owing to its high magneto-crystalline anisotropy ( $ À4 Â 10 5 J/m 3 ) [15].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, A u was proportional to the anisotropy energy K u , assuming that the TKE signal was proportional to the magnetization of the sample. 24 The anisotropy energy of the most anisotropic amorphous Fe-Si film was 15 2 ϫ 10 4 erg/ cm 3 and in the amorphous Co-Si film was 14 6 ϫ 10 3 erg/ cm 3 .…”
Section: Methodsmentioning
confidence: 98%
“…In the case of the Co-Si alloys, the easy axis is defined by the plane of incidence of the evaporated species for any Si concentration. 4,14 However, the Fe-Si amorphous alloys have a range of low Si concentrations where their easy axes does not point in such a direction, 15 and it can be oriented by externally applied magnetic fields of weak intensity ͑lower than 30 Oe͒ during film deposition. Since the anisotropy of Co-Si films, and Fe-Si with high enough Si concentrations, is unchanged by externally applied magnetic fields, it is proposed that its origin should be associated to the internal structure of the film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been attributed to novel mechanical, [1][2][3][4] magnetic [5][6][7][8] and catalytic [9][10][11] properties and excellent corrosion resistance [12][13][14][15][16][17] for these materials. Among magnetic amorphous materials, Cobased alloys are important and have been produced by various techniques including rapid quenching, 18,19) physical vapor deposition, 20) chemical or electroless plating 21,22) and electrodepostion.…”
Section: Introductionmentioning
confidence: 99%